The Implementation of the Qur'an in the Concept of Ijtihad by Substitute Heirs - Aisyah Aulia Madzkur; Ishaq Ishaq; Muhammad Faisol (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Islamic inheritance law is fundamentally oriented toward justice and the protection of vulnerable family members, yet its practical application often raises challenges in contemporary contexts. Specific Background: In Indonesia, grandchildren whose parents predeceased the testator are frequently excluded from inheritance despite close kinship ties, prompting the emergence of the substitute heir doctrine in Article 185 of the Compilation of Islamic Law (KHI). Knowledge Gap: Although this doctrine is normatively applied, its Qur’anic foundation—particularly the interpretation of QS. an-Nisā’ (4):33—and its ijtihad construction remain contested, as classical jurists largely rejected the notion of heir substitution. Aims: This study aims to analyze the Qur’anic implementation in the concept of substitute heirs, examine Hazairin’s ijtihad, and assess its legal implications in Indonesian inheritance law. Results: The findings demonstrate that the substitute heir concept represents a synthesis of Qur’anic reinterpretation, customary law, civil law influences, and Hazairin’s bilateral inheritance theory, positioning mawālī as descendants of predeceased heirs. Novelty: The study highlights that this concept constitutes not merely social adaptation but a reconstructive Qur’anic ijtihad strengthening the protection of orphaned grandchildren. Implications: The research underscores the need for firmer and more consistent enforcement of substitute heir provisions to ensure justice and legal certainty in inheritance distribution in Indonesia. Highlights: Emphasizes the role of ijtihad in reconstructing Qur’anic interpretation to address contemporary inheritance issues. Highlights the protection of orphaned grandchildren through the substitute heir concept in Indonesian Islamic law. Stresses the need for consistent legal enforcement to ensure justice and certainty in inheritance distribution. Keywords: Islamic Inheritance Law, Substitute Heirs, Ijtihad, Qur’anic Interpretation, Legal Reform